Optimum dose of sea cucumber (Stichopus chloronotus) extract for wound healing - Mazliadiyana M,; Nazrun AS,; Isa Naina Mohamed, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
In Malaysia, sea cucumber is also known as Gamat. Among the Malays, Gamat is frequently used as a traditional or folk medicine to relieve pain, to treat wounds and burns. It is also used as a tonic to provide extra energy. Stichopus chloronotus is one of the species of sea cucumber which is found in Malaysia. An experimental study was carried out to determine the optimum dose of aqueous extract of Stichopus chloronotus on the healing of wounds in rat model. A series of concentrations 0.1%, 0.5% and 1% aqueous extract emulsifying ointment mixed with Stichopus chloronotus was applied once a day for 10 days on the excision wound model. Changes in the wound area were measured using a caliper and photographs were taken on day 1, 3, 6, 8 and 10 after the wound creation. The wound reduction rate and macroscopic observation were evaluated to determine the optimum dose concentration. Results demonstrated that percentage of wound reduction and macroscopic observation of 0.5% aqueous extract Stichopus chloronotus emulsifying ointment mixed group was significantly higher than the other groups from day 6 following wound creation. In conclusion, 0.5% aqueous extract of Stichopus chloronotus emulsifying ointment mixture demonstrated the best dose for wound healing in a rat model.